Rancang Bangun Keamanan Kotak Amal dengan Akses Fingerprint Menggunakan ESP32-Cam dan Telegram Berbasis IOT - Diky Hermawan; Jufrizel Jufrizel; Aulia Ullah; Ahmad Faizal (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2023)
The charity box is one of the objects that is often the center of attention by thieves, the security of the charity box in current technological developments can be further developed, the creation of a charity box security tool with Fingerprint access using an IOT-based ESP32-cam is one of the developments that aims to improve security in charity box and reduce the rate of theft that occurs. The tool is made using Arduino UNO as the main microcontroller that processes data in this design and ESP32-cam as the recipient of commands from Arduino Uno and Telegram after which it sends data in the form of notifications in the form of photos and sentences describing the images that have been sent. Using 2 sensor inputs, namely the Fingerprint sensor to open the lid of the charity box door, if the fingerprint is registered, it sends a command to the Solenoid to open the charity box door, whereas when the fingerprint is not registered, the Solenoid will not open after that, ESP32-cam gets an order to capture the photo. sent to the telegram application and the Limit Switch sensor functions to detect the state of the charity box door when there is a forced opening that occurs at the door it will send data to Arduino UNO that there is a threat then the buzzer will sound. After testing the results obtained have a success rate of 100%, the ESP32-cam can receive orders to take pictures properly if one of the sensors used is active and can send data in the form of photos to the telegram application properly then the sensor used also works well well, the buzzer will sound when a forced opening is detected by the Limit Switch sensor. In this research it is hoped that it can improve the security of the charity box by capturing photos through the applied ESP32-Cam.